Synergistic effect of combined oyster peptide and ginseng extracts on anti-exercise-fatigue and promotion of sexual interest activity in male ICR mice. (November 2021) - Luo, Xianliang; Liu, Wangxin; Zhong, Hao; Yan, Yongqiu; Feng, Fengqin; Zhao, Minjie
Graphical abstract: Highlights: Novelty, a synergistic effect of OPGE on anti-fatigue and sexual ability was explored. OPGE promoted physical recovery and accelerated fatigue elimination. OPGE increased sexual behavior of male mice after exhausted swimming. OPGE enhanced the expression of testosterone synthesis related protease. Abstract: Traditionally, ginseng and oyster are regarded as biological tonics for enhancing vital energy. In this study, a post-exercise fatigue model and copulatory test were performed to evaluate the effects of combined oyster peptide and ginseng extracts (OPGE) on anti-fatigue and sexual function. The forced swimming time of mice was prolonged by taking OPGE. Moreover, the level of serum lactic acid, blood urea nitrogen, and lactate dehydrogenase activity were decreased, while the liver glycogen content and antioxidant ability in skeletal muscles were increased. Furthermore, OPGE statistically improved the sexual behavioral indexes of exercise-fatigue mice. The levels of testosterone and follicle-stimulating hormone in serum, and the expression of testosterone synthesis-related-protease in testis were increased by OPGE administration, while phosphodiesterase-5 content was decreased. Overall, our study suggested that OPGE could be a potential androgen-like dietary supplement to accelerate the elimination of fatigue and improve testosterone-deficiency symptom after intensive training.